Penentuan Tarif Layanan pada Badan Pengelola Usaha (BPU) Universitas Lampung - Rama Ardhy Prahbowo; Susi Sarumpaet; Usep Syaipudin (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
The Public Service Agency is an agency within the Government that was formed to provide services to the community in the form of supplying goods and/or services that are sold without prioritizing profit and in carrying out its activities based on the principles of efficiency and productivity. The results of calculating the basic price of the room using the Activity Based Costing System are, for a Single/Twin Bed Room Rp. 397,904, and for a Triple Bed Room Rp. 440,215. There is a higher price difference using the Activity Based Costing System , namely for a Single/Twin Bed Room of IDR 197,904 for a Triple Bed Room of IDR 190,215.The results of calculating the cost of the courtroom using the Activity Based Costing System is IDR 395,599 and IDR 395,454 for the traditional method. For the calculation of the Activity Based Costing System in the guest house meeting room, the results of calculating the basic price of the room with the Activity Based Costing System results in a higher calculation (overstate) compared to the basic price of the room which is determined by the traditional method, namely with a price difference of IDR 145.